Is it safe to drive a vehicle with a steering equipment positioned on the same side as the direction of the traffic – driving simulation experiments - Grzegorz Gudzbeler; Paweł Gromek; Andrzej Urban; Mariusz Nepelski (Journal of Modern Science, 2023)
Objectives For the purposes of the conducted research, the following main objective was defined: Examine how does the movement of RHD vehicles in RHT traffic affect the safety of road users.